Participatory social mapping as a territorial research methodology: a case study in the Afro-Colombian Pacific region - Bonfá Neto, Dorival; Suzuki, Júlio César (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Participatory social mapping contributes to understanding the referents constituted by the subjects and the meanings that constitute them, especially from their relationships with the territory. Thus, during the fieldwork focused on artisanal fishing activities and participatory workshops with students from the municipal school of Bahía Solano (Chocó, Colombia), whichincluded debates, map-making activities, and interviews, we seek to analyze the construction of the territory and the traditional Afro-Colombian territorialities in the Pacific based on their relationship with traditional practices and knowledge involved especially with fishing,which are often hidden or absent in official maps. It was noticed, then, that the visions and maps constructed by children and teenagers between 13 and 18 years of age from the fishingcommunity of Bahía Solano revealed the social and cultural awareness of these subjects, who perceive, to a great extent, many of the territorialities in which they are inserted and the relationship with traditional activities.